Design and optimization of dual-phase chain transmission system based on single tooth chain plate. Issue 2 (1st February 2023) - Cheng, Yabing; Chen, Luxiang; Ge, Pingyu; Chen, Xiaomin; Niu, Jiaxing
Abstract: Based on the meshing mechanism and design theory of the silent chain, a new type of dual-phase chain transmission system based on single tooth chain plate structure is innovated. The meshing design system of the chain transmission system is built through the parameter design of single tooth chain plate and dual-phase sprocket. Some dynamics parameters of the system can be obtained through dynamics simulation analysis, which has important reference value for the evaluation and improvement of the system. The simulation results show that the angular velocity fluctuation of the chain plate is small, and the average transverse fluctuation of the chain plate is 1.345 mm. It indicates that the transmission performance of the chain transmission system is stable, which proves the feasibility and rationality of the meshing design system. In order to further improve the transmission performance of the system, the single tooth chain plate and pin are optimized. By optimizing the shape and size of the single tooth chain plate and pin, the quality of the chain transmission system can be reduced by 23.30%, which can satisfy the lightweight design requirements. This research innovate a new type of chain transmission system, and broaden the research field of multi-variation of chain transmission system, and provide a scientific basis for further personalized research of chain transmission system.